If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 + 2(-8 + -8n) = -143 1 + (-8 * 2 + -8n * 2) = -143 1 + (-16 + -16n) = -143 Combine like terms: 1 + -16 = -15 -15 + -16n = -143 Solving -15 + -16n = -143 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '15' to each side of the equation. -15 + 15 + -16n = -143 + 15 Combine like terms: -15 + 15 = 0 0 + -16n = -143 + 15 -16n = -143 + 15 Combine like terms: -143 + 15 = -128 -16n = -128 Divide each side by '-16'. n = 8 Simplifying n = 8
| 5=4a+-7 | | -95=-8(3n-6)+1 | | 4x-2-7= | | 3a+b+5a+2b= | | 5x+10=305 | | -1-3(1+3r)=-31 | | X^2-3x+37=9x+5 | | 4X+3=2X+103 | | 81-3=n | | -5k+8(-2k-8)=-169 | | (-8x-5)(x+6)=(x+3)(-8x-8) | | 5a+4b+2a= | | -33=3(-3k-2) | | 10y+18=3(5-7)+5y | | Log[3](4x+3)=0 | | 5a+3b+2a= | | y+29=4y+48 | | 2a+5b+3a= | | -2m-4m+10= | | 5(k-2)=10(3k+5) | | Y=-55+4.5 | | log(3)(4x+3)=0 | | 6x-21=14x | | 3(2x+3)=75 | | 2x^2-3x+4+3x-x^2-6= | | 8w=-56 | | Y=4.5x-55 | | 16y=256 | | 2x^2+3-8x^2-5x+6-x= | | -4(x-6)+3(a-7)= | | 6(7x+3)+6x=306 | | -3(x+8)+2x(-4x+3)= |